A battery

By using a porous membrane and suitable silicon material particle size in lithium-ion secondary batteries, the battery energy density, fast charging performance and safety problems are solved, and the comprehensive improvement of high magnification, low expansion and safety performance is achieved.

CN119153895BActive Publication Date: 2025-02-25ZHUHAI COSMX POWER BATTERY CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411607361.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-12
Publication Date
2025-02-25
Estimated Expiration
2044-11-12

AI Technical Summary

Technical Problem

While improving energy density and fast charging performance, existing lithium-ion secondary batteries face problems such as reducing diaphragm needle puncture strength, self-discharge and safety performance. In addition, the silicon negative electrode material will cause volume expansion and contraction during charging and discharging, affecting the battery. rate performance and fast charging cycle performance.

Method used

A separator with a porous structure is adopted, and the ceramic layer includes inorganic particles, with a large porosity to improve ion transport capacity, and by controlling the average particle size of the silicon material and the size of the pores of the ceramic layer, a buffer space is provided to reduce the expansion rate of the battery. At the same time, the glue coating layer is cancelled to improve the specific energy of the battery.

Benefits of technology

The high-rate performance, fast charging and cycling performance and low expansion rate of the battery are achieved, improving the overall performance and safety of the battery, while reducing the cost of the diaphragm.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119153895B_ABST
    Figure CN119153895B_ABST
Patent Text Reader

Abstract

The present invention relates to the field of battery technology, and in particular to a battery. The battery includes a positive electrode sheet, a negative electrode sheet, an electrolyte, and a separator located between the positive electrode sheet and the negative electrode sheet, the separator includes a substrate and a ceramic layer located on one side or both sides of the substrate, the ceramic layer includes inorganic particles, the ceramic layer is a porous structure, the porous structure includes pores with a diameter of ≥0.5μm, and the coverage rate of pores with a diameter of ≥0.5μm on the surface of the ceramic layer is 10%-50%; the negative electrode sheet includes a negative electrode current collector and a negative electrode active material layer coated on one side or both sides of the negative electrode current collector, the negative electrode active material layer includes a negative electrode active material, the negative electrode active material includes a silicon material, and the average particle size D1 of the silicon material is 1μm-10μm; the battery satisfies the following relationship: 0.5≤D1 / D2≤5, wherein D2 is the average diameter of the pores with a diameter of ≥0.5μm in the ceramic layer, in μm. The battery of the present invention has the advantages of low expansion rate, high rate performance and good fast charging cycle performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of batteries, and in particular to a battery. Background Art

[0002] With the popularization of 3C products and the rise of the electric vehicle market, the demand for lithium-ion secondary batteries is increasing. For electric vehicles, battery life and fast charging are two very critical performance indicators. How to balance the fast charging performance of batteries while improving energy density has become very important.

[0003] As one of the two poles of the battery, the negative electrode directly affects the battery's energy density and fast charging performance. As a key component of lithium-ion secondary batteries, the separator directly affects the safety, rate and fast charging cycle performance of lithium-ion secondary batteries. Summary of the invention

[0004] The traditional solution to battery specific energy, fast charge cycle performance and rate performance is mainly to improve the porosity of the substrate and the ion conductivity of the diaphragm, thereby improving the battery rate performance and fast charge performance. However, as the porosity of the substrate increases, the puncture strength of the diaphragm will decrease, affecting the self-discharge, safety and other performance of the battery; at the same time, a layer of glue is coated on the surface of the diaphragm to improve the interface between the diaphragm and the positive active layer and the negative active layer, thereby improving the long cycle capacity of the battery. However, coating a layer of glue will reduce the fast charge performance of the battery to a certain extent. In addition, coating a layer of glue will increase the cost of the diaphragm. Silicon negative electrode material, as a high energy density battery material, has received widespread attention. However, silicon negative electrode materials will expand and contract in volume during the charge and discharge process, affecting the rate performance and fast charge cycle performance of the battery.

[0005] In order to solve the above technical problems existing in the prior art, the present invention provides a battery. The battery of the present invention has the advantages of low expansion rate, high rate performance and good fast charging cycle performance.

[0006] In order to achieve the above object, the present invention provides a battery, the battery comprises a positive electrode sheet, a negative electrode sheet, an electrolyte and a separator located between the positive electrode sheet and the negative electrode sheet, the separator comprises a substrate and a ceramic layer located on one side or both sides of the substrate, the ceramic layer comprises inorganic particles, the ceramic layer is a porous structure, the porous structure comprises pores with a diameter of ≥0.5 μm, and the coverage rate of the pores with a diameter of ≥0.5 μm on the surface of the ceramic layer is 10%-50%;

[0007] The negative electrode sheet includes a negative electrode current collector and a negative electrode active material layer coated on one side or both sides of the negative electrode current collector, the negative electrode active material layer includes a negative electrode active material, the negative electrode active material includes a silicon material, and the average particle size D1 of the silicon material is 1μm-10μm; the battery satisfies the following relationship: 0.5≤D1 / D2≤5, wherein D2 is the average diameter of the pores in the ceramic layer with a diameter ≥0.5μm, in μm.

[0008] Through the above technical solution, the present invention has at least the following advantages compared with the prior art:

[0009] The porosity of the diaphragm in the battery of the present invention is relatively large, and the ion transmission capacity is improved, thereby improving the rate performance and fast charging cycle performance of the battery. At the same time, through the coordinated cooperation of the diaphragm and the silicon material, the porous structure of the diaphragm provides a buffer space for the volume expansion and contraction of the silicon material, thereby reducing the expansion rate of the battery and improving the rate performance and fast charging cycle performance of the battery. At the same time, the diaphragm in the battery of the present invention does not need to be coated with a glue layer, thereby improving the specific energy of the battery.

[0010] Other features and advantages of the present invention will be described in detail in the following detailed description.

[0011] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article. BRIEF DESCRIPTION OF THE DRAWINGS

[0012] Figure 1 Shown is a SEM image of a separator (ceramic layer including a first polymer) in a battery according to an embodiment of the present invention.

[0013] Figure 2 Shown is a SEM image of a separator (the ceramic layer does not include the first polymer) in a battery according to an embodiment of the present invention.

[0014] Figure 3 Shown is a pore size distribution curve of the ceramic layer in Example 1 of the present invention.

[0015] Figure 4 FIG. 1 is a schematic cross-sectional view of a separator (a ceramic layer includes a first polymer) according to the present invention.

[0016] Figure 5 FIG. 1 is a schematic top view of a diaphragm (the ceramic layer includes a first polymer) of the present invention.

[0017] Figure 6FIG. 4 is a schematic cross-sectional view of a separator of the present invention (the ceramic layer does not include the first polymer).

[0018] Figure 7 FIG. 4 is a schematic top view of a separator of the present invention (the ceramic layer does not include the first polymer). DETAILED DESCRIPTION

[0019] The specific embodiments of the present invention are described in detail below. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present invention and are not used to limit the present invention. In this article, unless otherwise specified, the data range includes the endpoints. Data near the endpoint value (for example, a range of variation less than or equal to ±25% (for example, ±25%, ±20%, ±15%, ±10%, ±5% or ±1%) of the value) also belongs to the protection scope of the data range of the present invention.

[0020] It should be noted that the numerical expressions such as "first" and "second" in the present disclosure are only used to distinguish different substances or usage methods, and do not represent the difference in order.

[0021] The present invention provides a battery, the battery comprising a positive electrode sheet, a negative electrode sheet, an electrolyte and a separator located between the positive electrode sheet and the negative electrode sheet, the separator comprising a substrate and a ceramic layer located on one side or both sides of the substrate, the ceramic layer comprising inorganic particles, the ceramic layer being a porous structure, the porous structure comprising pores with a diameter of ≥0.5 μm, and the coverage of pores with a diameter of ≥0.5 μm on the surface of the ceramic layer being 10%-50%;

[0022] The negative electrode sheet includes a negative electrode current collector and a negative electrode active material layer coated on one side or both sides of the negative electrode current collector, the negative electrode active material layer includes a negative electrode active material, the negative electrode active material includes a silicon material, and the average particle size D1 of the silicon material is 1μm-10μm; the battery satisfies the following relationship: 0.5≤D1 / D2≤5, wherein D2 is the average diameter of the pores in the ceramic layer with a diameter ≥0.5μm, in μm.

[0023] Figure 1 and Figure 2 As shown, from Figure 1 and Figure 2 It can be seen that the ceramic layer is a porous structure, and Figure 1 The red circles in the figure are holes with a diameter of ≥0.5μm. One red circle indicates one hole with a diameter of ≥0.5μm. It should be noted that the red circle only indicates the Figure 1 The pores with a diameter of ≥0.5 μm do not indicate Figure 1 All pores with a diameter ≥ 0.5 μm.

[0024] like Figure 4 , Figure 5 , Figure 6 and Figure 7 As shown, the diaphragm includes a substrate 1 and a ceramic layer 2 located on one side or both sides of the substrate 1, the ceramic layer 2 includes inorganic particles 21, and the ceramic layer 2 is a porous structure, wherein 23 is a hole.

[0025] The porous structure may include pores having a diameter ≥ 0.5 μm (eg, 0.5 μm, 1 μm, 1.5 μm, 2 μm, 2.5 μm, 3 μm, 3.5 μm, 4 μm, 4.5 μm, or 5 μm).

[0026] D2 is the average diameter of the pores in the ceramic layer with a diameter ≥ 0.5 μm.

[0027] In the present invention, the term "diameter" and "average diameter" have different meanings. The term "diameter" refers to the diameter of a single pore. For example, a pore with a diameter ≥ 0.5 μm means a pore with a diameter ≥ 0.5 μm. The term "average diameter" refers to the average value of the diameters of all pores in a system. For example, the average diameter of pores with a diameter ≥ 0.5 μm in a ceramic layer means the average value of the diameters of all pores with a diameter ≥ 0.5 μm in a system.

[0028] Both the diameter and the average diameter can be obtained by SEM testing. For example, it can be obtained by testing in the following manner: using an electrolytic emission scanning electron microscope (S-3400N manufactured by Hitachi, Ltd.), observe the surface of the ceramic layer at a magnification of 50,000 times. The image size at this time is 2.5μm×1.8μm. It should be noted that the number of pixels is 1,280 pixels×960 pixels, and the size of 1 pixel is 2nm×1.9nm. For the diameter, a square or rectangle with the smallest area that completely surrounds one hole is drawn on the obtained image, that is, a square or rectangle in which the end of the hole is connected to the four sides of the square or rectangle. In the case of a square, the length of one side is set as the diameter of the hole, and in the case of a rectangle, the length of the long side (major axis diameter) is set as the diameter of the hole. For any 81 holes, the diameter of each hole is measured, and the average value of the number is set as the average diameter. It should be noted that when more than 81 holes are observed in the captured image, the number average of any 81 holes in the image is set as the average diameter of the holes. When 81 holes are not observed in the image, multiple images are captured and the number average of the total 81 holes is set as the average diameter.

[0029] The average particle size D1 of the silicon material may be 1 μm-10 μm (eg, 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, or 10 μm).

[0030] In the present invention, the term "average particle size" refers to the average value of the diameters of all particles in a system. The average particle size can be measured in the following manner: using an electrolytic emission scanning electron microscope (S-3400N manufactured by Hitachi, Ltd.), observe the surface of the porous layer at a magnification of 50,000 times. The image size at this time is 2.5μm×1.8μm. It should be noted that the number of pixels is 1,280 pixels×960 pixels, and the size of 1 pixel is 2nm×1.9nm. For the average particle size, a square or rectangle with the smallest area that completely surrounds one particle is drawn on the obtained image, that is, a square or rectangle in which the end of the particle is connected to the four sides of the square or rectangle. In the case of a square, the length of one side is set as the particle size, and in the case of a rectangle, the length of the long side (major axis diameter) is set as the particle size. For any 81 particles, measure their respective particle sizes, and set their number average as the average particle size. It should be noted that when more than 81 particles are observed in the captured image, the number average of any 81 particle sizes in the image is set as the average particle size. When 81 particles are not observed in the image, multiple images are captured and the number average of the total 81 particle sizes is set as the average particle size.

[0031] The coverage of the pores with a diameter of ≥0.5 μm on the surface of the ceramic layer is 10%-50% (for example, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45% or 50%). The coverage of the pores with a diameter of ≥0.5 μm on the surface of the ceramic layer represents the ratio of the sum of the orthogonal projection areas of the pores with a diameter of ≥0.5 μm on the surface of the ceramic layer on the surface of the substrate to the orthogonal projection area of ​​the ceramic layer on the surface of the substrate.

[0032] In the present invention, the coverage of the pores with a diameter of ≥0.5 μm on the surface of the ceramic layer can be obtained by testing in the following manner: for example, by using a scanning electron microscope (SEM) test, specifically: using SEM to obtain a microscopic image of the surface of the ceramic layer, randomly dividing an area of ​​100 μm in the image 2 Take an area (for example, 100µm×100µm), divide this area into 100*100 uniform squares, if the coverage area of ​​the holes with diameter ≥0.5μm in the square exceeds half of the square area, it means that the square is occupied by holes with diameter ≥0.5μm, otherwise it means that the square is not occupied by holes with diameter ≥0.5μm, count the number of squares occupied by holes with diameter ≥0.5μm, record the total number of squares occupied by holes with diameter ≥0.5μm as X, then coverage = (X / 100*100)*100%, repeat the above operation 5 times, and take the average value of the 5 times as the coverage of holes with diameter ≥0.5μm on the surface of the ceramic layer.

[0033] The ceramic layer of the diaphragm in the battery of the present invention is a porous structure. By controlling the coverage rate of pores with a diameter of ≥0.5μm in the porous structure, the porosity of the diaphragm can be increased, the ion transmission capacity of the diaphragm can be increased, and thus the rate performance and fast charging cycle performance of the battery can be improved. At the same time, by controlling the average particle size of the silicon material and 0.5≤D1 / D2≤5 (for example, 0.5, 1, 1.5, 2, 2.5, 3, 3.5, 4, 4.5, or 5), the size of the silicon particles can be matched with the macropores (pores with a diameter of ≥0.5μm) in the ceramic layer of the diaphragm, so that the diaphragm can provide a certain expansion space for the volume expansion of the silicon particles, reduce the expansion rate of the battery, and improve the structural stability of the negative electrode active material layer, thereby improving the rate performance and fast charging performance of the battery. At the same time, when the battery is rapidly charged and discharged, the metal ion complex can be quickly and orderly embedded and released on the negative electrode side, thereby improving the fast charging cycle performance of the battery. In addition, the ceramic layer of the diaphragm of the present invention has adhesion and can replace the glue layer to improve the stability between the diaphragm and the positive electrode active layer and the negative electrode active layer, thereby improving the specific energy of the battery while avoiding the adverse effects of the glue layer on the fast charging performance of the battery.

[0034] When the coverage rate of pores with a diameter of ≥0.5μm on the surface of the ceramic layer is less than 10%, the ion permeability of the diaphragm is low, and the fast charging cycle and rate performance of the battery cannot be effectively improved; when the coverage rate of pores with a diameter of ≥0.5μm on the surface of the ceramic layer is higher than 50%, the heat resistance of the diaphragm is low, and the safety performance of the battery cannot be guaranteed.

[0035] When D1 is lower than 1μm, the average particle size of the silicon material is too small, resulting in an excessively large specific surface area of ​​the silicon material, causing excessive side reactions between the negative electrode active material and the electrolyte, thereby affecting the long cycle performance of the battery; when D1 is higher than 10μm, the average particle size of the silicon material is too large, resulting in an excessively small specific surface area of ​​the silicon material, causing the surface of the negative electrode active material to be too small and without sufficient channels for charging and discharging, thereby affecting the rate performance of the battery.

[0036] When D1 / D2 is less than 0.5, on the one hand, the average particle size of the silicon material is too small, resulting in a large specific surface area of ​​the silicon material, which makes the side reaction between the negative electrode active material and the electrolyte too large, thus affecting the long cycle performance of the battery; on the other hand, the average diameter of the pores with a diameter ≥ 0.5 μm in the diaphragm ceramic layer is too large, which makes the diaphragm have poor heat resistance, thus affecting the battery safety performance; when D1 / D2 is greater than 5, the ceramic layer of the diaphragm does not have sufficient pore area to provide space for the silicon material to expand, so that the battery expands too much and affects the battery fast charging cycle performance.

[0037] In the present invention, by controlling the coverage of pores with a diameter of ≥0.5 μm in the porous structure, the average particle size of the silicon material, and the ratio of the average particle size of the silicon material to the average diameter of pores with a diameter of ≥0.5 μm in the ceramic layer, the battery has the advantages of low expansion rate, high rate performance, and good fast charge cycle performance compared to the prior art. In order to further improve the effect, one or more of the technical features may be further optimized.

[0038] In one example, 1≤D1 / D2≤4.

[0039] In one example, D1 is 2 μm-8 μm.

[0040] In one example, D2 is 0.5 μm-10 μm (eg, 0.5 μm, 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, or 10 μm).

[0041] In one example, D2 is 1 μm-8 μm.

[0042] According to a specific implementation, D1 is 2 μm-8 μm, D2 is 1 μm-8 μm, and the battery satisfies the following relationship: 1≤D1 / D2≤4.

[0043] In one example, the coverage of pores with diameters ≥ 0.5 μm on the surface of the ceramic layer is 20%-40%.

[0044] In one example, the silicon material includes at least one of elemental silicon, silicon-oxygen compounds, silicon-carbon compounds, silicon-nitrogen compounds, and silicon alloys.

[0045] In one example, the silicon carbon composite includes Si / C.

[0046] In one example, the silicon-oxygen compound includes SiOx / C.

[0047] The ceramic layer may or may not include the first polymer.

[0048] like Figure 6 and Figure 7 As shown, the ceramic layer may not include the first polymer.

[0049] like Figure 4 and Figure 5 The illustrated ceramic layer 2 may also include a first polymer 22 .

[0050] In one example, the ceramic layer further includes a first polymer. The first polymer has adhesive properties, so the ceramic layer has adhesion.

[0051] like Figure 1As shown, the green circle indicates the first polymer, and one green circle indicates one first polymer. It should be noted that the green circle only indicates Figure 1 The first polymer in the middle part does not mean Figure 1 All of the first polymer.

[0052] In one example, the peeling force of the ceramic layer is ≥25 N / m.

[0053] In the present invention, the peeling force can be tested in the following manner: a 2.5 cm wide 3M tape is pressed on the diaphragm using a 1 kg pressing block for 1 minute, the prepared sample diaphragm and the 3M tape are placed at an angle of 180 degrees on a universal stretching machine at a speed of 100 mm / min and a test displacement of 50 mm, and the minimum peeling force that can achieve a displacement of 50 mm between the diaphragm and the 3M tape is recorded as the peeling force N (unit N / m) between the ceramic layer and the substrate.

[0054] In one example, within a range of 100 μm×100 μm selected at random on the surface of the ceramic layer, the number of holes with a diameter of ≥0.5 μm is 10-800 (e.g., 10, 50, 100, 200, 300, 400, 500, 600, 700 or 800). Controlling the number of holes with a diameter of ≥0.5 μm within a range of 100 μm×100 μm selected at random on the surface of the ceramic layer to be within the above range can ensure that the coverage of holes with a diameter of ≥0.5 μm on the surface of the ceramic layer is 10%-50%, thereby increasing the porosity of the diaphragm and improving the rate performance and fast charge cycle performance of the battery. When the number of pores with a diameter ≥0.5μm within a range of 100μm×100μm selected at any time on the surface of the ceramic layer is less than 10, the coverage rate of pores with a diameter ≥0.5μm on the surface of the ceramic layer is less than 10%, the ion permeability of the diaphragm is low, and the fast charging cycle and rate performance of the battery cannot be effectively improved; when the number of pores with a diameter ≥0.5μm within a range of 100μm×100μm selected at any time on the surface of the ceramic layer is higher than 800, the coverage rate of pores with a diameter ≥0.5μm on the surface of the ceramic layer is higher than 50%, the heat resistance of the diaphragm is low, and the safety performance of the battery cannot be guaranteed.

[0055] In one example, the number of holes with a diameter of ≥0.5 μm in an area of ​​100 μm×100 μm randomly selected on the surface of the ceramic layer is 50-500.

[0056] According to a specific embodiment, the coverage rate of holes with diameter ≥ 0.5 μm on the surface of the ceramic layer is 20%-40%, and the number of holes with diameter ≥ 0.5 μm in an arbitrarily selected range of 100 μm×100 μm on the surface of the ceramic layer is 50-500.

[0057] In one example, based on the total volume of the pores in the ceramic layer, the volume of pores with a diameter of ≥0.5 μm accounts for 20%-70% (for example, 20%, 30%, 40%, 50%, 60% or 70%). Controlling the volume of pores with a diameter of ≥0.5 μm in the total volume of the pores in the ceramic layer within the above range can, on the one hand, make the diaphragm have good heat resistance, thereby improving the safety performance of the battery; on the other hand, it can increase the porosity of the diaphragm, so that the diaphragm has good ion permeability, thereby improving the fast charge cycle and rate performance of the battery. When the volume of pores with a diameter of ≥0.5 μm in the total volume of the pores in the ceramic layer accounts for less than 20%, the porosity of the diaphragm is low, so that the ion permeability of the diaphragm is insufficient, and the fast charge cycle and rate performance of the battery cannot be effectively improved; when the volume of pores with a diameter of ≥0.5 μm in the total volume of the pores in the ceramic layer accounts for more than 70%, the heat resistance of the diaphragm is low, and the safety performance of the battery cannot be guaranteed.

[0058] In the present invention, the volume fraction of pores with a diameter of ≥0.5 μm can be obtained by testing in the following manner: a mercury intrusion testing method can be used, specifically, a mercury intrusion testing method is used to obtain a pore size distribution curve of the entire diaphragm (such as Figure 3 As shown in the figure), the pore size of the substrate in the diaphragm does not exceed 0.08μm. Therefore, the pore size distribution curve of the ceramic layer can be obtained by eliminating the pore sizes ≤0.08μm in the pore size distribution curve of the diaphragm in the pore size distribution curve of the overall diaphragm. The ratio of the integral area of ​​pores greater than or equal to 0.5μm in the pore size distribution curve of the ceramic layer to the total integral area of ​​the pore size distribution curve of the ceramic layer is calculated, which is the volume proportion of pores with a diameter ≥0.5μm in the total volume of pores in the ceramic layer.

[0059] In one example, based on the total volume of the pores in the ceramic layer, the volume of pores with a diameter of ≥0.5 μm accounts for 30%-60%.

[0060] In one example, the coverage of the ceramic layer on the surface of the substrate is 50%-100% (e.g., 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85%, 90%, 95% or 100%). Controlling the coverage of the ceramic layer on the surface of the substrate within the above range can make the diaphragm have good thermal stability, thereby making the battery have excellent safety performance. When the coverage of the ceramic layer on the surface of the substrate is less than 50%, the thermal stability of the diaphragm is poor, thereby reducing the safety performance of the battery.

[0061] In one example, the coverage rate of the ceramic layer on the surface of the substrate is 60%-90%.

[0062] In the present invention, the coverage of the ceramic layer on the substrate surface represents the ratio of the orthographic projection area of ​​the ceramic layer on the substrate surface to the substrate surface area. Figure 1 As shown, the holes in the porous structure will partially expose the substrate, while partially will not expose the substrate, and the orthographic projection area of ​​the ceramic layer on the surface of the substrate will exclude the area of ​​the holes exposed by the substrate.

[0063] In one embodiment, the surface density of the ceramic layer is 1 g / m 2 -8g / m 2 (For example, 1g / m 2 , 2g / m 2 , 3g / m 2 , 4g / m 2 , 5g / m 2 , 6g / m 2 , 7g / m 2 or 8g / m 2 ).

[0064] In one embodiment, the surface density of the ceramic layer is 1.5 g / m 2 -6g / m 2 .

[0065] In the present invention, the surface density refers to the single-sided surface density. For example, the surface density of the ceramic layer refers to the surface density of the side (i.e., the side with the ceramic layer) when there is a ceramic layer on the surface of one side of the substrate; when there are ceramic layers on the surfaces of both sides of the substrate, the surface densities of the ceramic layers on both sides of the diaphragm are the same, and the surface density of the ceramic layer is the surface density of any one side.

[0066] In one example, within a range of 100 μm×100 μm arbitrarily selected on the surface of the ceramic layer, the number of the first polymer is 0-600 (for example, 0, 10, 50, 100, 150, 200, 250, 300, 350, 400, 450, 500, 550 or 600). When the number of the first polymer is 0, it means that the first polymer does not exist in the ceramic layer. Even if the first polymer does not exist in the ceramic layer, the ceramic layer still has adhesion. Controlling the number of the first polymer within a range of 100 μm×100 μm arbitrarily selected on the surface of the ceramic layer to be within the above range can make the diaphragm have good ion permeability, thereby improving the fast charging cycle and rate performance of the battery. When the number of the first polymer is higher than 600 within a range of 100 μm×100 μm arbitrarily selected on the surface of the ceramic layer, the thermal stability of the diaphragm is very poor, thereby reducing the safety performance of the battery.

[0067] In one example, within an arbitrarily selected area of ​​100 μm×100 μm on the surface of the ceramic layer, the number of the first polymers is 30-500.

[0068] In one example, based on the total weight of the ceramic layer, the weight content W2 of the first polymer is 0-15% (e.g., 0, 0.1%, 0.5%, 1%, 3%, 5%, 8%, 10%, 13% or 15%). When the weight content of the first polymer in the ceramic layer is 0, it means that the ceramic layer does not include the first polymer.

[0069] In one example, based on the total weight of the ceramic layer, the weight content W2 of the first polymer is 5%-12%.

[0070] In one example, the first polymer includes a first monomer and a second monomer and optionally ("optionally" means that it may or may not exist) a third monomer. The first polymer has adhesive properties and can replace the coating layer to improve the stability between the separator and the positive electrode active layer and the negative electrode active layer.

[0071] In one example, the first monomer includes one or more of an acrylonitrile monomer, a styrene monomer, and an acrylate monomer.

[0072] In one example, the acrylic acid ester monomer includes one or more of methyl methacrylate, methyl acrylate, ethyl acrylate, butyl acrylate, isooctyl acrylate, lauryl acrylate, and octadecyl acrylate.

[0073] In one example, the styrene monomer includes one or more of styrene, methylstyrene, triphenylethylene and 4-methylstyrene.

[0074] In one example, the acrylonitrile monomer includes one or more of acrylonitrile, triphenylacrylonitrile, 3-cyclopentylacrylonitrile and 3,3-(diphenyl)acrylonitrile.

[0075] In one example, the second monomer includes one or more of dimethyl acrylamide, diethyl acrylamide, divinyl benzene, trimethylol propane triacrylate, ethylene glycol dimethacrylate, ethylene glycol diacrylate, triethylene glycol dimethacrylate, and tetraethylene glycol dimethacrylate.

[0076] In one example, the third monomer includes one or more of acrylic acid, butadiene, methacrylic acid, acrylamide, hydroxymethyl acrylamide, hydroxyethyl acrylamide, isopropyl acrylamide, glycidyl (meth)acrylate, and allyl glycidyl ester.

[0077] In one example, the inorganic particles include one or more of aluminum oxide, boehmite, magnesium oxide, magnesium hydroxide, barium sulfate, barium titanate, zinc oxide, calcium oxide, silicon dioxide, silicon carbide, and boron nitride.

[0078] In one example, the ceramic layer further includes a membrane binder and a thickener.

[0079] In one example, the thickener includes one or more of methyl cellulose (CMC), sodium carboxymethyl cellulose (CMC-Na), and lithium carboxymethyl cellulose (CMC-Li).

[0080] In one example, the membrane binder includes one or more of polytetrafluoroethylene, polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene, polyimide, polyacrylonitrile, polymethyl (meth)acrylate, aramid resin, poly (meth)acrylic acid, styrene-butadiene rubber (SBR), polyvinyl alcohol, polyvinyl acetate and carboxyethyl cellulose.

[0081] In one example, based on the total weight of the ceramic layer, the weight content of the inorganic particles is 85%-98% (e.g., 85%, 88%, 90%, 92%, 95% or 98%), the weight content of the thickener is 1%-5% (e.g., 1%, 2%, 3%, 4% or 5%), and the weight content of the diaphragm binder is 1%-10% (e.g., 1%, 3%, 5%, 8% or 10%).

[0082] In one example, based on the total weight of the ceramic layer, the weight content of the inorganic particles is 86%-93%, the weight content of the thickener is 1.5%-4%, and the weight content of the diaphragm binder is 2%-6%.

[0083] In one example, the battery satisfies the following relationship: 2≤D3 / H1≤5 (for example, 2, 2.5, 3, 3.5, 4, 4.5 or 5), wherein D3 is the average particle size of the first polymer, in μm; H1 is the thickness of the ceramic layer, in μm. Controlling D3 / H1 within the above range can make the size of the first polymer protruding from the surface of the ceramic layer more suitable. On the one hand, it can make the ceramic layer have better adhesion, so that the diaphragm has higher interface stability with the positive electrode active layer and the negative electrode active layer, further improving the long cycle performance of the battery; on the other hand, it can keep the distance between the ceramic layer and the positive electrode active layer and the negative electrode active layer at a more suitable size, so that the diaphragm has a good interface distance with the positive electrode active layer and the negative electrode active layer, thereby improving the fast charging and long cycle performance of the battery. When D3 / H1<2, due to the small average particle size of the first polymer, there is not enough first polymer to maintain good contact with the positive active layer and the negative active layer, thereby affecting the interface adhesion between the diaphragm and the positive active layer and the negative active layer, and the fast charging and long cycle performance of the battery cannot be effectively improved; when D3 / H1>5, due to the large average particle size of the first polymer, the size of the first polymer protruding on the surface of the ceramic layer is too large, thereby making the distance between the diaphragm and the positive active layer and the negative active layer too large, affecting the interface stability between the diaphragm and the positive active layer and the negative active layer, and the fast charging and long cycle performance of the battery cannot be effectively improved.

[0084] It is understandable that in the process of preparing the diaphragm, the thickness of the ceramic layer cannot be absolutely uniform, so in the present invention, the thickness H1 of the ceramic layer is the maximum thickness of the ceramic layer. The thickness of the ceramic layer can be obtained by SEM testing.

[0085] In one example, 1.5≤D3 / H1≤4.

[0086] In one example, in one example, D3 is 2 μm-10 μm (eg, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, or 10 μm).

[0087] In one example, D3 is 3 μm-8 μm.

[0088] In one example, H1 is 1 μm-5 μm (eg, 1 μm, 2 μm, 3 μm, 4 μm, or 5 μm).

[0089] In one example, H1 is 1.5 μm-4 μm.

[0090] According to a specific implementation, D3 is 3 μm-8 μm, H1 is 1.5 μm-4 μm, and the diaphragm satisfies the following relationship: 1.5≤D3 / H1≤4.

[0091] In one example, the battery satisfies the following relationship: 1<D2 / D4<20 (for example, 1.1, 3, 5, 8, 10, 13, 15, 18 or 19.9), wherein D4 is the average particle size of the inorganic particles, in μm. Controlling D2 / D4 within the above range, on the one hand, can allow a large number of pores to exist in the diaphragm, further improve the porosity of the diaphragm, thereby further improving the ion transport performance of the diaphragm, and further improving the fast charging performance of the battery; on the other hand, it can increase the packing density between inorganic particles, thereby increasing the puncture strength and thermal stability of the diaphragm, thereby reducing the self-discharge of the battery, improving the safety performance of the battery, and leaving the self-discharge and safety performance of the battery unaffected. When D2 / D4≤1, the packing density between inorganic particles is too low, the thermal stability of the diaphragm is poor, and the safety performance of the battery is low; when D2 / D4≥20, the pore size is too large, the thermal stability of the diaphragm is poor, and the safety performance of the battery is low.

[0092] In one example, the battery satisfies the following relationship: 2≤D2 / D4≤16.

[0093] In one example, D4 ​​is 0.1 μm-3 μm (eg, 0.1 μm, 0.5 μm, 1 μm, 1.5 μm, 2 μm, 2.5 μm, or 3 μm).

[0094] In one example, D4 ​​is 0.5 μm-2.5 μm.

[0095] According to a specific implementation, D2 is 1 μm-8 μm, D4 is 0.5 μm-2.5 μm, and the battery satisfies the following relationship: 2≤D2 / D4≤16.

[0096] According to a specific implementation, D3 is 3 μm-8 μm, H1 is 1.5 μm-4 μm, D2 is 1 μm-8 μm, D4 is 0.5 μm-2.5 μm, and the diaphragm satisfies the following relationship: 1.5≤D3 / H1≤4 and 2≤D2 / D4≤16.

[0097] In one example, the battery satisfies the following relationship: 0.5≤W3 / N1≤10 (for example, 0.5, 1, 2, 3, 4, 5, 6, 7, 8, 9 or 10), wherein W3 is the weight content of the silicon material based on the total weight of the negative electrode active material, in units of %; N1 is the coverage of the first polymer in the ceramic layer on the surface of the ceramic layer, in units of %. Controlling W3 / N1 within the above range, on the one hand, can increase the adhesion between the separator and the negative electrode sheet, thereby providing good interface stability between the separator and the negative electrode sheet; on the other hand, can enable the battery to have a higher energy density, and at the same time, can still maintain the interface stability between the separator and the negative electrode sheet during rapid charge and discharge, thereby enabling the battery to have good cycle performance.

[0098] In the present invention, the coverage of the first polymer in the ceramic layer on the surface of the ceramic layer refers to the ratio of the orthographic projection area of ​​the first polymer in the ceramic layer on the surface of the substrate to the orthographic projection area of ​​the ceramic layer on the surface of the substrate.

[0099] In the present invention, the coverage of the first polymer on the surface of the ceramic layer can be obtained by testing in the following manner: for example, by using a scanning electron microscope (SEM) to test, specifically: using SEM to obtain a microscopic image of the surface of the ceramic layer, randomly dividing an area of ​​100 μm in the image 2 An area (for example, 100µm×100µm) is divided into uniform squares of 100*100. If the area covered by the first polymer in the square exceeds half of the area of ​​the square, it means that the square is occupied by the first polymer. Otherwise, it means that the square is not occupied by the first polymer. By counting the number of squares occupied by the first polymer, the total number of squares occupied by the first polymer is recorded as X, then the coverage rate = (X / 100*100)*100%. Repeat the above operation 5 times, and the average value of the 5 times is the coverage rate of the first polymer on the surface of the ceramic layer.

[0100] In one example, 1≤W3 / N1≤8.

[0101] In one example, N1 is 0%-50% (eg, 0%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, or 50%).

[0102] In one example, N1 is 10%-40%.

[0103] In one example, W3 is 1%-100% (eg, 1%, 5%, 10%, 20%, 30%, 40%, 50%, 60%, 70%, 80%, 90% or 100%). When W3 is 100%, it indicates that the negative electrode active material is a silicon material.

[0104] In one example, W3 is 5%-50%.

[0105] According to a specific implementation, N1 is 5%-20%, W3 is 5%-95%, and the battery satisfies the following relationship: 1≤W3 / N1≤8.

[0106] In one example, the negative electrode active material further includes a carbon-based material, and the carbon-based material includes graphite and / or hard carbon.

[0107] In one example, based on the total weight of the negative electrode active material, the weight content of the carbon-based material is 0%-99% (e.g., 0%, 0.1%, 1%, 5%, 10%, 20%, 30%, 40%, 50%, 60%, 70%, 80%, 90% or 99%). When the weight content of the carbon-based material in the negative electrode active material is 0%, it means that there is no carbon-based material in the negative electrode active material.

[0108] In one example, based on the total weight of the negative electrode active material, the weight content of the carbon-based material is 5%-95%.

[0109] In one example, the negative electrode active material layer further includes a negative electrode conductor and a negative electrode binder.

[0110] In one example, the negative electrode conductive agent is one or more of conductive carbon black, carbon nanotubes, conductive graphite, and graphene.

[0111] In one example, the negative electrode binder is one or more of polyvinylidene fluoride (PVDF), acrylic acid-modified PVDF, polyacrylate polymers, polytetrafluoroethylene, perfluorosulfonic acid ionomers, polyacrylonitrile, polyimide, styrene-butadiene rubber, and styrene-acrylic rubber.

[0112] In one example, based on the total weight of the negative electrode active layer, the weight content of the negative electrode active material is 90%-98% (for example, 90%, 92%, 95% or 98%), the weight content of the negative electrode conductor is 0%-5% (for example, 0%, 0.1%, 0.5%, 1%, 2%, 3%, 4% or 5%), and the weight content of the negative electrode binder is 1%-5% (for example, 1%, 2%, 3%, 4% or 5%).

[0113] In one example, based on the total weight of the negative electrode active layer, the weight content of the negative electrode active material is 92%-97%, the weight content of the negative electrode conductive agent is 1%-4%, and the weight content of the negative electrode binder is 1.5%-4.5%.

[0114] In one example, the electrolyte includes an organic solvent, and the organic solvent includes at least two of dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), propylene carbonate (PC), ethylene carbonate (EC), diethyl carbonate (DEC), propyl propionate (PP), ethyl propionate (EP) and ethyl acetate (EA).

[0115] In one example, the organic solvent includes a first organic solvent and a second organic solvent.

[0116] In one example, the first organic solvent includes one or more of dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), propyl propionate (PP), ethyl propionate (EP) and ethyl acetate (EA).

[0117] In one example, the second organic solvent is propylene carbonate (PC) and / or ethylene carbonate (EC).

[0118] In one example, the weight ratio of the first organic solvent to the weight ratio of the second organic solvent is (0.05-20):1. Controlling the weight ratio of the first organic solvent to the second organic solvent within the above range can make the electrolyte have a suitable viscosity and good ion conductivity, so that the battery has a higher long cycle performance and better fast charging performance. When the weight ratio of the first organic solvent to the second organic solvent is lower than 0.05:1, the content of the second organic solvent is too high, resulting in too high viscosity of the electrolyte, which reduces the fast charging performance of the battery; when the weight ratio of the first organic solvent to the second organic solvent is higher than 20:1, the content of the first organic solvent is too high, resulting in low ion conductivity, which reduces the long cycle performance of the battery.

[0119] In one example, the weight ratio of the first organic solvent to the second organic solvent is (0.1-10):1.

[0120] In another example, the organic solvent includes ethyl methyl carbonate, ethyl acetate, and ethylene carbonate.

[0121] In one example, the weight ratio of ethyl methyl carbonate, ethyl acetate and ethylene carbonate in the organic solvent is (10%-70%): (10%-70%): (15%-40%).

[0122] It can be understood that the weight content of ethyl methyl carbonate in the organic solvent can be in the range of 10%-70% (for example, 10%, 20%, 30%, 40%, 50%, 60% or 70%), the weight content of ethyl acetate in the organic solvent can be in the range of 10%-70% (for example, 10%, 20%, 30%, 40%, 50%, 60% or 70%), and the weight content of ethylene carbonate in the organic solvent can be in the range of 15%-40% (for example, 15%, 20%, 25%, 30%, 35% or 40%), but it needs to be satisfied that the sum of the weight content of ethyl methyl carbonate, the weight content of ethyl acetate and the weight content of ethylene carbonate in the organic solvent is 100%.

[0123] In one example, based on the total weight of the electrolyte, the weight content of the organic solvent is 64%-86% (eg, 64%, 65%, 70%, 75%, 80%, 85% or 86%).

[0124] In one example, based on the total weight of the electrolyte, the weight content of the organic solvent is 70%-82%.

[0125] In one example, the electrolyte further includes LiFSI and optionally an additive.

[0126] In one example, the additive includes fluoroethylene carbonate (FEC), 1,3-propane sultone (PS), vinylene carbonate (VC), lithium difluorophosphate (LiPO2F2), lithium bis(oxalatoborate) (LiBOB), lithium difluorooxalatoborate (LiODFB), lithium difluorooxalatophosphate (LiODFP), lithium tetrafluoroborate (LiBF4), and lithium tetrafluorooxalatophosphate (LiTFOP).

[0127] In one example, based on the total weight of the electrolyte, the weight content of LiFSI is 2%-20% (e.g., 2%, 5%, 10%, 15% or 20%), and the weight content of the additive is 0%-10%. When the weight content of the additive in the electrolyte is 0%, it means that there is no additive in the electrolyte.

[0128] In one example, based on the total weight of the electrolyte, the weight content of LiFSI is 3%-9%, and the weight content of the additive is 1%-8%.

[0129] In one example, the electrolyte further includes a lithium salt.

[0130] In one example, the lithium salt includes at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, and lithium perchlorate.

[0131] In one example, based on the total weight of the electrolyte, the weight content of the lithium salt is 12%-30% (eg, 12%, 15%, 18%, 20%, 22%, 25%, 28% or 30%).

[0132] In one example, based on the total weight of the electrolyte, the weight content of the lithium salt is 15%-25%.

[0133] In one example, at 60°C-90°C, the first polymer is immersed in the solvent for 2min-10min, and the solubility of the first polymer is ≤50%. Controlling the solubility of the first polymer within the above range can make the ceramic layer have better adhesion, so that the diaphragm has higher interface stability with the positive electrode active layer and the negative electrode active layer, further improving the long cycle performance of the battery. When the solubility of the first polymer is higher than 50%, the amount of the first polymer retained in the ceramic layer after the battery is hot pressed is small, resulting in insufficient first polymer to maintain good contact with the positive electrode active layer and the negative electrode active layer, thereby affecting the interface adhesion between the diaphragm and the positive electrode active layer and the negative electrode active layer, and failing to effectively improve the fast charge and long cycle performance of the battery.

[0134] The solvent may be the organic solvent described in the present invention, or may be the electrolyte solution comprising the organic solvent described in the present invention.

[0135] In one example, at 60° C.-90° C., the first polymer is immersed in the solvent for 2 min-10 min, and the solubility of the first polymer is 1%-20%.

[0136] In the present invention, the solubility can be tested by the following method: taking EMC as the solvent, take a first polymer with a weight of M1, add it to an EMC beaker with a content of 20*M1, place the beaker in an oven at 80°C for 10 minutes, take out the remaining first polymer and dry it, weigh the remaining first polymer and record the weight as M2, then the solubility of the first polymer in the solvent EMC is (M1-M2) / M1*100%.

[0137] The positive electrode sheet may be a conventional positive electrode sheet in the art. For example, the positive electrode sheet includes a positive electrode current collector and a positive electrode active layer located on at least one surface of the positive electrode current collector.

[0138] There is no special restriction on the positive electrode active layer, and the positive electrode active layer may include components such as positive electrode active material, positive electrode conductive agent, positive electrode binder, etc. according to the conventional composition in the art. Among them, the components such as positive electrode active material, positive electrode conductive agent, positive electrode binder, etc. may be selected from conventional materials in the art, for example, the positive electrode active material may be selected from one or more of lithium nickel oxide, lithium titanate, lithium cobalt oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, lithium iron phosphate, and lithium manganese oxide; the positive electrode conductive agent may be selected from one or more of conductive carbon black, carbon nanotubes, conductive graphite, and graphene; the positive electrode binder may be selected from one or more of polyvinylidene fluoride (PVDF), acrylic acid-modified PVDF, polyacrylate polymers, polytetrafluoroethylene, perfluorosulfonic acid ionomers, polyacrylonitrile, polyimide, styrene-butadiene rubber, and styrene-acrylic rubber.

[0139] In one example, the positive electrode active material is selected from lithium iron phosphate or lithium iron phosphate doped and coated with two or more elements of Al, Mg, Mn, Cr, Ti, and Zr.

[0140] In one example, based on the total weight of the positive electrode active layer, the weight content of the positive electrode active material is 90%-98% (for example, 90%, 91%, 92%, 93%, 94%, 95%, 96%, 97% or 98%), the weight content of the positive electrode conductor is 1%-5% (for example, 1%, 2%, 3%, 4% or 5%), and the weight content of the positive electrode binder is 1%-5% (for example, 1%, 2%, 3%, 4% or 5%).

[0141] In one example, based on the total weight of the positive electrode active layer, the weight content of the positive electrode active material is 92%-97%, the weight content of the positive electrode conductor is 1.5%-4%, and the weight content of the positive electrode binder is 1.5%-4%.

[0142] The diaphragm and battery of the present invention can be prepared by the following method:

[0143] Preparation of the initial diaphragm: Inorganic particles, water or deionized water, a thickener and a diaphragm binder are mixed to prepare an aqueous slurry, an initial first polymer and a second polymer are added to the aqueous slurry to prepare a ceramic slurry, and the ceramic slurry is coated on one side or both sides of the substrate to prepare the initial diaphragm. The initial diaphragm includes a substrate and a ceramic layer located on one side or both sides of the substrate, and the ceramic layer includes inorganic particles and the initial first polymer.

[0144] In one example, the weight ratio of the inorganic particles, the thickener, and the membrane binder is (85%-98%): (1%-5%): (1%-10%).

[0145] In one example, the weight ratio of the initial first polymer, the weight of the second polymer and the weight of the inorganic particles is (0%-15%): (2%-30%): (98%-70%). It is understood that the weight content of the initial first polymer can be in the range of 0%-15% (for example, 0%, 0.1%, 0.5%, 1%, 3%, 5%, 8%, 10%, 13% or 15%), the weight content of the second polymer can be in the range of 2%-30% (for example, 2%, 5%, 10%, 15%, 20%, 25% or 30%), and the weight content of the inorganic particles can be in the range of 98%-70% (for example, 98%, 95%, 90%, 85%, 80%, 75% or 70%), but it needs to be satisfied that the sum of the weight content of the polymer and the weight content of the inorganic particles is 100%. When the weight content of the initial first polymer is 0%, it means that the first polymer does not exist.

[0146] In one example, the average particle size of the initial first polymer is 2 μm-10 μm (eg, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm or 10 μm).

[0147] In one example, the average particle size of the second polymer is 0.5 μm-5 μm (eg, 0.5 μm, 1 μm, 2 μm, 3 μm, 4 μm, or 5 μm).

[0148] In one example, the initial first polymer includes a first monomer and a second monomer and optionally ("optionally" means that it may or may not be present) a third monomer.

[0149] In one example, the second polymer includes a fourth monomer and a fifth monomer.

[0150] In one example, the fourth monomer includes one or more of an acrylonitrile monomer, a styrene monomer, and an acrylate monomer.

[0151] In one example, the acrylic acid ester monomer includes one or more of methyl methacrylate, methyl acrylate, ethyl acrylate, butyl acrylate, isooctyl acrylate, lauryl acrylate, and octadecyl acrylate.

[0152] In one example, the styrene monomer includes one or more of styrene, methylstyrene, triphenylethylene and 4-methylstyrene.

[0153] In one example, the acrylonitrile monomer includes one or more of acrylonitrile, triphenylacrylonitrile, 3-cyclopentylacrylonitrile and 3,3-(diphenyl)acrylonitrile.

[0154] In one example, the fifth monomer includes one or more of acrylic acid, butadiene, methacrylic acid, acrylamide, hydroxymethyl acrylamide, hydroxyethyl acrylamide, isopropyl acrylamide, glycidyl (meth)acrylate, and allyl glycidyl ester.

[0155] At 60°C-90°C, the first polymer can be soaked in the solvent for 2min-10min (for example, 2min, 3min, 4min, 5min, 6min, 7min, 8min, 9min or 10min), and the solubility of the first polymer is ≤50%. The second polymer can be soaked in the solvent for 2min-10min (for example, 2min, 3min, 4min, 5min, 6min, 7min, 8min, 9min or 10min), and the second polymer is completely dissolved. Since the first polymer is partially dissolved and the second polymer is completely dissolved, during the hot pressing process of the battery, the completely dissolved second polymer and the partially dissolved first polymer form a large number of pores in the ceramic layer of the diaphragm. Among them, part of the insoluble first polymer remains in the ceramic layer of the diaphragm. Therefore, the pores with a surface diameter ≥0.5μm in the ceramic layer are formed by the partially dissolved first polymer and the completely dissolved second polymer.

[0156] The solvent may be the organic solvent described in the present invention, or may be the electrolyte solution comprising the organic solvent described in the present invention.

[0157] The first polymer and the second polymer have adhesive properties and can replace the coating layer to improve the stability between the separator and the positive electrode active layer and the negative electrode active layer, thereby reducing or even avoiding the adverse effects of the coating layer on the fast charging performance of the battery.

[0158] Preparation of the battery: Assemble the initial separator with a positive electrode sheet (a conventional positive electrode sheet in the art), a negative electrode sheet (a conventional negative electrode sheet in the art) and an electrolyte to form a battery.

[0159] The prepared battery is hot pressed, wherein the hot pressing conditions include: a hot pressing temperature of 60°C-90°C (for example, 60°C, 65°C, 70°C, 75°C, 80°C, 85°C or 90°C), a hot pressing pressure of 0.1MPa-1.5MPa (for example, 0.1MPa, 0.3MPa, 0.5MPa, 0.8MPa, 1MPa, 1.3MPa or 1.5MPa), and a hot pressing time of 10min-60min (10min, 20min, 30min, 40min, 50min or 60min).

[0160] In the battery after hot pressing, since the initial first polymer is partially dissolved in the electrolyte and the second polymer is completely dissolved in the electrolyte, the first polymer exists in the ceramic layer of the diaphragm and the second polymer does not exist. The partially dissolved first polymer and the completely dissolved second polymer form a large number of pores in the middle and / or on the surface of the ceramic layer, thereby obtaining the diaphragm comprising a large number of pores described in the present invention. It is understandable that the initial first polymer is of the same type as the first polymer in the ceramic layer, but the average particle size of the initial first polymer is different from the average particle size of the first polymer. In the process of preparing batteries, hot pressing is an indispensable step in preparing batteries, which can also be referred to as formation in the art.

[0161] The coating layer in the prior art has adhesive properties, and during the preparation of the battery, it can improve the stability between the diaphragm and the positive electrode active layer and the negative electrode active layer, ensuring that the battery core will not become soft and affect the process efficiency of the battery. However, during the use of the battery, the coating layer will reduce the fast charging performance of the battery. In the diaphragm in the battery of the present invention, during the preparation of the battery, the ceramic layer in the diaphragm includes a first polymer and a second polymer, and the first polymer and the second polymer both have adhesive properties, and can replace the coating layer to improve the stability between the diaphragm and the positive electrode active layer and the negative electrode active layer. During the use of the battery (which has been hot pressed), the first polymer is partially dissolved in the electrolyte, and the second polymer is completely dissolved in the electrolyte, reducing the adverse effects of the first polymer and the second polymer on the fast charging performance of the battery.

[0162] The battery may be a lithium ion secondary battery.

[0163] The present invention will be described in detail below by way of examples. The examples described in the present invention are only a part of the examples of the present invention, rather than all of the examples. Based on the examples in the present invention, all other examples obtained by ordinary technicians in the field without creative work are within the scope of protection of the present invention.

[0164] The following examples are provided to illustrate the separator and battery of the present invention.

[0165] Example Group I is used to illustrate that the ceramic layer in the separator of the present invention does not include the first polymer.

[0166] Example I-1

[0167] (1) Preparation of diaphragm

[0168] Component preparation: Substrate: polyethylene, thickness 9 μm;

[0169] Ceramic layer: inorganic particles: aluminum oxide; thickener: sodium carboxymethyl cellulose; diaphragm binder: poly (meth) acrylic acid; second polymer: methyl acrylate-acrylic acid copolymer; wherein the weight ratio of the inorganic particles, the thickener and the diaphragm binder is 92%:3%:5%; the weight ratio of the second polymer to the inorganic particles is 7%:93%.

[0170] Inorganic particles, water, a thickener and a membrane binder are mixed to prepare an aqueous slurry (with a solid content of 28%), a second polymer is added to the aqueous slurry to prepare a ceramic slurry, and the ceramic slurry is coated on both sides of the substrate to prepare an initial membrane.

[0171] (2) Preparation of electrolyte

[0172] Ingredients preparation: Lithium salt: lithium hexafluorophosphate, 12.5 parts by weight;

[0173] Organic solvent: 76.5 parts by weight, wherein the weight ratio of ethyl methyl carbonate (EMC), ethyl acetate (EA) and ethylene carbonate (EC) is 35%:35%:30%;

[0174] LiFSi, 6.5 parts by weight;

[0175] Additives: vinylene carbonate (VC), 4.5 parts by weight;

[0176] In a glove box filled with argon (water content <10ppm, oxygen content <1ppm), the organic solvents were mixed evenly to obtain a mixed solution 1, additives were added to the mixed solution 1 to obtain a mixed solution 2, LiFSi and lithium salt were slowly added to the mixed solution 2, and the mixture was stirred evenly to obtain a non-aqueous electrolyte.

[0177] (3) Preparation of positive electrode

[0178] The positive electrode active material (NCM), the positive electrode binder (polyvinylidene fluoride (PVDF)), and the positive electrode conductive agent (acetylene black) are mixed in a weight ratio of 96.5:1.5:2.0, N-methylpyrrolidone (NMP) is added, and the mixture is stirred under the action of a vacuum mixer until the mixed system becomes a positive electrode slurry with uniform fluidity; the positive electrode slurry is evenly coated on the surface of both sides of an aluminum foil with a thickness of 10 μm; the coated aluminum foil is baked in an oven with 5 different temperature gradients (95℃±5℃, 100℃±5℃, 103℃±5℃, 100℃±5℃, 95℃±5℃), and then dried in an oven at 120℃ for 8 hours, and then rolled and cut to obtain the required positive electrode sheet.

[0179] (4) Preparation of negative electrode

[0180] The negative electrode active material (graphite and silicon oxide weight ratio of 60:40, that is, W3 is 40%), the negative electrode conductive agent (including single-walled carbon nanotubes (SWCNT) 0.2 weight parts, conductive carbon black (SP) 1 weight part), the negative electrode binder (including sodium carboxymethyl cellulose (CMC-Na) 1 weight part, styrene-butadiene rubber (SBR) 2.5 weight parts) are mixed in a weight ratio of 95.3:1.2:3.5, and a slurry is made by a wet process (adding water to the mixture formed by the above mixing, stirring under the action of a vacuum stirrer until the mixture becomes a negative electrode slurry with uniform fluidity), and coated on the surface of both sides of the negative electrode collector (copper foil), and dried (temperature: 85°C, time: 5h), rolled and die-cut to obtain a negative electrode sheet.

[0181] (5) Preparation of lithium-ion secondary batteries

[0182] The positive electrode sheet of step (3), the separator of step (1), and the negative electrode sheet of step (4) are wound to obtain a bare cell without liquid injection, and 5MPa is applied to the wound core for 10 minutes; the bare cell is placed in an outer packaging foil, and the electrolyte of step (2) is injected into the dried bare cell, and the process includes vacuum packaging, standing, hot pressing (wherein the hot pressing temperature is 80°C, the hot pressing pressure is 1MPa, and the hot pressing time is 40 minutes. After hot pressing, the first polymer in the initial separator is partially dissolved, and the second polymer is completely dissolved. The partially dissolved first polymer and the completely dissolved second polymer form a large number of pores in the middle and surface of the ceramic layer of the separator to obtain the separator of the present invention), shaping, sorting, and other processes to obtain the desired lithium ion secondary battery. Wherein, the separator after hot pressing, based on the total weight of the ceramic layer, has an inorganic particle weight content of 85.6%, a first polymer weight content of 6.9%, a separator binder weight content of 4.7%, and a thickener weight content of 2.8%. See Table I-1 for details.

[0183] Example I-2 Group

[0184] This group of embodiments is used to illustrate the impact when D1 changes.

[0185] This example group is carried out with reference to Example I-1, except that D1 / D2 is changed by adjusting D1, as shown in Table I-1 for details.

[0186] Example I-3 Group

[0187] This group of embodiments is used to illustrate the impact when D4 changes.

[0188] This example group is carried out with reference to Example I-1, except that D2 / D4 is changed by adjusting D4, as shown in Table I-1 for details.

[0189] Example I-4 Group

[0190] This group of embodiments is used to illustrate the impact when D1 / D2 and D2 / D4 are changed.

[0191] This example group was carried out with reference to Example I-1, except that D1 / D2 and D2 / D4 were changed, see Table I-1 for details.

[0192] Example I-5 Group

[0193] This group of embodiments is used to illustrate the impact when EMC:EA:EC is changed.

[0194] This example group was carried out with reference to Example I-1, except that EMC:EA:EC was changed, see Table I-1 for details.

[0195] Example I-6 Group

[0196] This group of examples is used to illustrate the effects produced when the weight ratio of the first organic solvent to the second organic solvent is changed.

[0197] This example group was carried out with reference to Example I-1, except that the weight ratio of the first organic solvent to the second organic solvent was changed, as shown in Table I-1 for details.

[0198] Comparative Example I-1

[0199] The same process is carried out as in Example I-1, except that D1 / D2<0.5. For details, see Table I-1.

[0200] Comparative Example I-2

[0201] The same process is carried out as in Example I-1, except that D1 / D2>5. For details, see Table I-1.

[0202] Comparative Example I-3

[0203] The same process is carried out as in Example I-1, except that D1 is 12 μm. For details, see Table I-1.

[0204] Comparative Example I-4

[0205] Component preparation: Substrate: polyethylene, thickness 9 μm;

[0206] Ceramic layer: inorganic particles: aluminum oxide (1 μm); thickener: sodium carboxymethyl cellulose; diaphragm binder: poly (meth) acrylic acid; wherein the weight ratio of the inorganic particles, the thickener and the diaphragm binder is 92%:3%:5%.

[0207] Inorganic particles, water, a thickener and a separator binder are mixed to prepare an aqueous slurry (with a solid content of 28%), and the aqueous slurry is coated on both sides of the substrate.

[0208] Table I-1

[0209]

[0210]

[0211] *Same as Example I-1.

[0212] The Example II group is used to illustrate that the ceramic layer in the separator of the present invention includes a first polymer.

[0213] Example II-1

[0214] The method was carried out with reference to Example I-1, except that the diaphragm was changed, as follows:

[0215] (1) Preparation of diaphragm

[0216] Component preparation: Substrate: polyethylene, thickness 9 μm;

[0217] Ceramic layer: inorganic particles: aluminum oxide; thickener: sodium carboxymethyl cellulose; diaphragm binder: poly (meth) acrylic acid; initial first polymer: methyl methacrylate-diethylacrylamide-butadiene copolymer; second polymer: methyl acrylate-acrylic acid copolymer; wherein the weight ratio of the inorganic particles, the thickener and the diaphragm binder is 92%:3%:5%; the weight ratio of the initial first polymer, the second polymer and the inorganic particles is 7%:7%:86%.

[0218] Inorganic particles, water, a thickener and a membrane binder are mixed to prepare an aqueous slurry (with a solid content of 28%), a first polymer and a second polymer are added to the aqueous slurry to prepare a ceramic slurry, and the ceramic slurry is coated on both sides of a substrate to prepare an initial membrane.

[0219] Example II-2

[0220] The method is carried out in accordance with Example II-1, except that the weight proportion of the organic solvent remains unchanged, and the organic solvent is adjusted to consist of a first organic solvent (EMC) and a second organic solvent (EA), wherein the weight ratio of the first organic solvent to the second organic solvent is 1:1. For details, see Table II-1 and Table II-2.

[0221] Example II-3

[0222] This embodiment is used to illustrate that different parameter value combinations can still achieve the effects of the present invention.

[0223] This example is carried out with reference to Example II-1, and specifically see Table II-1 and Table II-2.

[0224] Example II-4

[0225] This embodiment is used to illustrate that different parameter value combinations can still achieve the effects of the present invention.

[0226] Refer to Example II-2, and see Table II-1 and Table II-2 for details.

[0227] Example II-5 Group

[0228] This group of embodiments is used to illustrate the impact caused by changes in D1 / D2.

[0229] This example group was carried out with reference to Example II-1, except that D1 / D2 was changed, see Table II-1 and Table II-2 for details.

[0230] Example II-6 Group

[0231] This group of examples is used to illustrate the impact when D2 / D4 changes.

[0232] This example group was carried out with reference to Example II-1, except that D2 / D4 was changed, as shown in Table II-1 and Table II-2 for details.

[0233] Example II-7 Group

[0234] This group of examples is used to illustrate the impact produced when D3 / H1 changes.

[0235] This example group was carried out with reference to Example II-1, except that D3 / H1 was changed, as shown in Table II-1 and Table II-2 for details.

[0236] Example II-8 Group

[0237] This set of examples is used to illustrate the effects of changing the specific selection of the first polymer.

[0238] This example group is carried out with reference to Example II-1, except that the specific selection of the first polymer is changed, as shown in Table II-1 and Table II-2.

[0239] Example II-9 Group

[0240] This set of examples is used to illustrate the effects of changing the specific selection of the second polymer.

[0241] This example group is carried out with reference to Example II-1, except that the specific selection of the second polymer is changed, as shown in Table II-1 and Table II-2.

[0242] Example II-10 Group

[0243] This group of embodiments is used to illustrate the impact caused by changes in EMC:EA:EC.

[0244] This example group was carried out with reference to Example II-1, except that EMC:EA:EC was changed. For details, see Table II-1 and Table II-2.

[0245] Example II-11 Group

[0246] This group of examples is used to illustrate the influence produced when the weight ratio of the first organic solvent to the second organic solvent is changed.

[0247] This example group was carried out with reference to Example II-2, except that the weight ratio of the first organic solvent to the second organic solvent was changed, as shown in Table II-1 and Table II-2 for details.

[0248] Example II-12 Group

[0249] This group of embodiments is used to illustrate the impact caused by changes in W3 / N1.

[0250] This example group is carried out with reference to Example II-1, except that W3 / N1 is changed, see Table II-1 and Table II-2 for details.

[0251] Example II-13 Group

[0252] This group of embodiments is used to illustrate the impact caused by changes in the volume ratio of pores with a diameter ≥ 0.5 μm in the ceramic layer.

[0253] This example group is carried out with reference to Example II-1, except that the volume percentage of pores with a diameter ≥ 0.5 μm in the ceramic layer is changed, see Table II-1 and Table II-2 for details.

[0254] Comparative Example II-1

[0255] The same procedure is carried out as in Example II-1, except that D1 / D2<0.5. For details, see Table II-1 and Table II-2.

[0256] Comparative Example II-2

[0257] The same procedure is carried out as in Example II-1, except that D1 / D2>5. For details, see Table II-1 and Table II-2.

[0258] Comparative Example II-3

[0259] The same procedure is carried out as in Example II-1, except that D1 is 12 μm. For details, see Table II-1 and Table II-2.

[0260] Table II-1

[0261]

[0262] *Same as Example II-1.

[0263] Table II-2

[0264]

[0265]

[0266] *Same as Example II-1.

[0267] Test Case

[0268] The diaphragms and lithium-ion secondary batteries obtained in the examples and comparative examples were tested as follows:

[0269] (1) Diaphragm shrinkage test

[0270] Take a diaphragm sample of 15cm*15cm length, pierce two holes with a diameter of 0.5mm at an interval of 10cm along the length direction of the diaphragm, and bake the sample in an oven at 150±2℃ for 1h. The distance between the two holes before baking is L1, and the distance between the two holes after baking is L2. Thermal shrinkage = (L1-L2) / L1*100%.

[0271] (2) 130℃ and 150℃ furnace temperature test

[0272] The lithium-ion secondary battery is heated in a convection air box at a starting temperature of (25±3)℃, a temperature change rate of (5±2)℃ / min, and the temperature is raised to (130±2)℃ and (150±2)℃ respectively. The test is terminated after 60 minutes of holding, and the battery status at (130±2)℃ and (150±2)℃ is recorded respectively. There are 30 batteries in each sample. If there is no explosion and / or fire, it means "pass", and if there is explosion or fire, it means "fail". The result is expressed as "number of passes / 30", for example, "30 / 30" means that all batteries have passed, and "10 / 30" means that 10 batteries out of 30 batteries have failed. It should be noted that the test result of "30 / 30" at a furnace temperature of 130℃ indicates that the safety performance of the lithium-ion secondary battery is not affected.

[0273] (3) Fast charging cycle test

[0274] Place the lithium-ion secondary battery in a (25±2)℃ environment and let it stand for 2-3 hours. When the battery body reaches (25±2)℃, record the battery thickness as T1. The battery is charged at a 3C constant current with a cutoff current of 0.05C. After the battery is fully charged (100% SOC), let it sit for 5 minutes and then discharge it at a 3C constant current to a cutoff voltage of 3.0V. Record the highest discharge capacity of the first three cycles as the initial capacity Q. When the cycle reaches 800 times, test the battery thickness as T2 and record the last discharge capacity of the battery Q1. The capacity retention rate (%) = Q1 / Q×100%, and the thickness expansion rate (%) = [(T2-T1) / T1]×100%.

[0275] (4) Rate performance test

[0276] Place the lithium-ion secondary battery at 25℃±2℃ for 4h, discharge it to 2.2V at 0.5C, charge it to the upper limit voltage (4.25V) at 0.5C, and record the cell capacity Q2; discharge the fully charged cell at 10C constant current at 25℃±2℃ to 2.5V, and record the cell capacity Q3. The capacity retention rate = Q3 / Q2*100%.

[0277] (5) Energy density WED test

[0278] Weigh the prepared finished battery at 25°C to obtain the battery weight;

[0279] The prepared finished battery was charged to full charge (100% SOC) at constant current and constant voltage at 25°C, with a charging current of 0.5C, charged to 4.25V, a cut-off current of 0.05C, and then discharged to 2.5V at 0.5C. The discharged capacity was recorded as the battery capacity.

[0280] Calculate the weight energy density (Wh / Kg) = (battery capacity * platform voltage) / battery weight.

[0281] (6) K value test

[0282] Place the lithium-ion secondary battery at 25℃±2℃ for 4h, discharge at 0.5C to 2.5V, charge at 0.5C to 4.25V, place at 45℃±2℃ for 48h, record the voltage V1, then place at 25±2℃ for 72h, record the voltage V2, K value = (V1-V2) / 72, in mV / h.

[0283] The specific results are recorded in Table 3.

[0284] Table 3

[0285]

[0286]

[0287] It can be seen from Table 3 that the thermal shrinkage rate of the diaphragm of the embodiment is low, the 130°C furnace temperature test results of the battery are all passed, the 150°C furnace temperature test results are good, the cycle capacity retention rate is high, the thickness expansion rate is low, the 10C rate discharge capacity retention rate is high, and the K value remains basically unchanged, indicating that the battery of the present invention reduces the expansion rate of the battery and improves the rate performance and fast charging cycle performance of the battery by controlling the coverage rate of pores with a diameter ≥0.5μm in the porous structure, the average particle size of the silicon material, and the ratio of the average particle size of the silicon material to the average diameter of pores with a diameter ≥0.5μm in the ceramic layer.

[0288] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A battery, characterized in that: The battery comprises a positive electrode sheet, a negative electrode sheet, an electrolyte and a separator located between the positive electrode sheet and the negative electrode sheet, wherein the separator comprises a substrate and a ceramic layer located on one or both sides of the substrate, wherein the ceramic layer comprises inorganic particles, and the ceramic layer is a porous structure, wherein the porous structure comprises pores with a diameter of ≥0.5 μm, and the coverage rate of the pores with a diameter of ≥0.5 μm on the surface of the ceramic layer is 10%-50%; The negative electrode sheet includes a negative electrode current collector and a negative electrode active material layer coated on one side or both sides of the negative electrode current collector, the negative electrode active material layer includes a negative electrode active material, the negative electrode active material includes a silicon material, and the average particle size D1 of the silicon material is 1 μm-10 μm; the battery satisfies the following relationship: 0.5≤D1 / D2≤5, wherein D2 is the average diameter of the pores of the ceramic layer with a diameter ≥0.5 μm, in μm; Wherein, on the scanned image, a square or rectangle with the smallest area that completely surrounds a hole is depicted, the length of one side of the square or the length of the long side of the rectangle is the diameter of the hole, and the number average of the diameters of any 81 holes is the average diameter of the hole; on the scanned image, a square or rectangle with the smallest area that completely surrounds a silicon material particle is depicted, the length of one side of the square or the length of the long side of the rectangle is the particle size of the silicon material, and the number average of the particle sizes of any 81 particles is the average particle size of the silicon material; a microscopic image of the surface of the ceramic layer is obtained by using SEM, and in the microscopic image of the surface of the ceramic layer, any 100 μm 2 The area is divided into uniform squares of 100*100. The number X of squares occupied by holes with a diameter ≥0.5μm is counted, and the coverage rate is measured = (X / 100*100)*100%. If the coverage area of ​​holes with a diameter ≥0.5μm in the square exceeds half of the square area, it means that the square is occupied by holes with a diameter ≥0.5μm.

2. The battery according to claim 1, wherein 1≤D1 / D2≤4; and / or, D1 is 2 μm-8 μm; and / or, D2 is 0.5 μm-10 μm; and / or, the coverage of pores with a diameter of ≥0.5 μm on the surface of the ceramic layer is 20%-40%; And / or, the silicon material includes at least one of elemental silicon, silicon-oxygen compounds, silicon-carbon composites, silicon-nitrogen composites and silicon alloys; And / or, the negative electrode active material further includes graphite and / or hard carbon.

3. The battery according to claim 2, wherein D2 is 1μm-8μm.

4. The battery according to claim 1 or 2, wherein The battery satisfies the following relationship: 1<D2 / D4<20, wherein D4 is the average particle size of the inorganic particles, in μm; and / or, the inorganic particles include one or more of aluminum oxide, boehmite, magnesium oxide, magnesium hydroxide, barium sulfate, barium titanate, zinc oxide, calcium oxide, silicon dioxide, silicon carbide, and boron nitride; and / or, within an arbitrarily selected range of 100 μm×100 μm on the surface of the ceramic layer, the number of holes with a diameter ≥ 0.5 μm is 10-800; and / or, based on the total volume of the pores in the ceramic layer, the volume of pores with a diameter of ≥0.5 μm accounts for 20%-70%; And / or, the coverage of the ceramic layer on the surface of the substrate is 50%-100%; And / or, the surface density of the ceramic layer is 1g / m 2 -8g / m 2 .

5. The battery according to claim 4, wherein The number of holes with a diameter of ≥0.5 μm in an arbitrarily selected area of ​​100 μm×100 μm on the surface of the ceramic layer is 50-500; and / or, based on the total volume of the pores in the ceramic layer, the volume of pores with a diameter of ≥0.5 μm accounts for 30%-60%; And / or, the coverage of the ceramic layer on the surface of the substrate is 60%-90%; And / or, the surface density of the ceramic layer is 1.5 g / m 2 -6g / m 2 .

6. The battery according to claim 4, wherein D4 is 0.1μm-3μm.

7. The battery according to claim 6, wherein D4 is 0.5μm-2.5μm.

8. The battery according to claim 4, wherein The ceramic layer also includes a first polymer.

9. The battery according to claim 8, wherein The first polymer includes a first monomer and a second monomer and optionally a third monomer, wherein the first monomer includes one or more of an acrylonitrile monomer, a styrene monomer and an acrylate monomer; the second monomer includes one or more of dimethyl acrylamide, diethyl acrylamide, divinyl benzene, trimethylolpropane triacrylate, ethylene glycol dimethacrylate, ethylene glycol diacrylate, triethylene glycol dimethacrylate and tetraethylene glycol dimethacrylate; the third monomer includes one or more of acrylic acid, butadiene, methacrylic acid, acrylamide, hydroxymethyl acrylamide, hydroxyethyl acrylamide, isopropyl acrylamide, glycidyl (meth)acrylate and allyl glycidyl ester.

10. The battery according to claim 9, wherein The acrylic acid ester monomers include one or more of methyl methacrylate, methyl acrylate, ethyl acrylate, butyl acrylate, isooctyl acrylate, lauryl acrylate and octadecyl acrylate.

11. The battery according to claim 9, wherein The styrene monomer includes one or more of styrene, methylstyrene, triphenylethylene and 4-methylstyrene.

12. The battery according to claim 9, wherein The acrylonitrile monomers include one or more of acrylonitrile, triphenyl acrylonitrile, 3-cyclopentyl acrylonitrile and 3,3-(diphenyl) acrylonitrile.

13. The battery according to claim 8, wherein In an arbitrarily selected area of ​​100 μm×100 μm on the surface of the ceramic layer, the number of the first polymers is 0-600; And / or, based on the total weight of the diaphragm, the weight content W2 of the first polymer is 0-15%.

14. The battery according to claim 13, wherein In an arbitrarily selected area of ​​100 μm×100 μm on the surface of the ceramic layer, the number of the first polymers is 30-500; And / or, based on the total weight of the diaphragm, the weight content W2 of the first polymer is 5%-12%.

15. The battery according to any one of claims 8 to 13, wherein The battery satisfies the following relationship: 2≤D3 / H1≤5, wherein D3 is the average particle size of the first polymer, in μm; H1 is the thickness of the ceramic layer, in μm.

16. The battery according to claim 15, wherein D3 is 2μm-10μm.

17. The battery according to claim 16, wherein: D3 is 3μm-8μm.

18. The battery according to claim 15, wherein H1 is 1μm-5μm.

19. The battery according to claim 18, wherein H1 is 1.5μm-4μm.

20. The battery according to claim 15, wherein The battery satisfies the following relationship: 0.5≤W3 / N1≤10, wherein W3 is the weight content of the silicon material based on the total weight of the negative electrode active material, in units of %; and N1 is the coverage of the first polymer in the ceramic layer on the surface of the ceramic layer, in units of %.

21. The battery according to claim 20, wherein 1≤W3 / N1≤8.

22. The battery according to claim 20, wherein N1 is 0%-50%.

23. The battery according to claim 22, wherein N1 is 10%-40%.

24. The battery according to claim 20, wherein W3 is 1%-100%.

25. The battery according to claim 24, wherein W3 is 5%-50%.

26. The battery according to claim 1 or 2, wherein The electrolyte includes an organic solvent, and the organic solvent includes at least two of dimethyl carbonate, ethyl methyl carbonate, propylene carbonate, ethylene carbonate, diethyl carbonate, propyl propionate, ethyl propionate and ethyl acetate.

27. The battery according to claim 26, wherein The organic solvent includes a first organic solvent and a second organic solvent, the first organic solvent includes one or more of dimethyl carbonate, ethyl methyl carbonate, diethyl carbonate, propyl propionate, ethyl propionate and ethyl acetate, and the second organic solvent includes propylene carbonate and / or ethylene carbonate; the weight ratio of the first organic solvent to the second organic solvent is (0.05-20):

1.

28. The battery according to claim 27, wherein The weight ratio of the first organic solvent to the second organic solvent is (0.1-10):

1.

29. The battery according to claim 28, wherein Based on the total weight of the electrolyte, the weight content of the organic solvent is 64%-86%.

30. The battery according to claim 29, wherein Based on the total weight of the electrolyte, the weight content of the organic solvent is 70%-82%.

31. The battery according to claim 26, wherein The organic solvent includes ethyl methyl carbonate, ethyl acetate and ethylene carbonate.

32. The battery according to claim 31, wherein The weight ratio of ethyl methyl carbonate, ethyl acetate and ethylene carbonate in the organic solvent is (10%-70%): (10%-70%): (15%-40%).

33. The battery according to claim 26, wherein The electrolyte further includes LiFSI and optionally an additive, wherein the additive includes one or more of fluoroethylene carbonate, 1,3-propane sultone, vinylene carbonate, lithium difluorophosphate, lithium bisoxalatoborate, lithium difluorooxalatoborate, lithium difluorooxalatophosphate, lithium tetrafluoroborate, and lithium tetrafluorooxalatophosphate.

34. The battery according to claim 33, wherein Based on the total weight of the electrolyte, the weight content of LiFSI is 2%-20%, and the weight content of the additive is 3%-9%.

35. The battery according to any one of claims 8 to 14, wherein At 60° C.-90° C., the first polymer is immersed in the solvent for 2 min-10 min, and the solubility of the first polymer is ≤50%.

36. The battery according to claim 35, wherein At 60° C.-90° C., the first polymer is immersed in the solvent for 2 min-10 min, and the solubility of the first polymer is 1%-20%.

Citation Information

Patent Citations

  • Battery

    CN119133778A

  • Diaphragm and battery

    CN119153896A